Bed-ridden Patients with Low Socio-Economic Status and Role of Traditional Thai Massage Practitioner Assistant in Khonburi, Nakhon Ratchasima Province, Thailand - Numsangkul, Sakawduan; Aekplakorn, Wichai (Journal of Health Science of Thailand, 2017)
Patients with bed-ridden conditions especially those with low socioeconomic status are among the most vulnerable group subjecting to be neglected in receiving adequate care. The short-term consequences are complications and permanent disability. The objective of this study was to assess the role of traditional Thai massage practitioner assistants (TTMPA) in home rehabilitation for bed-ridden patients in Khonburi district, Nakhon-Ratchasima province in 2014-2015. Seventy patients in sub-acute state following stroke attack or severe injury with home-bound or bed- ridden conditions were taken care by multidisciplinary team and additional visit by the TTMPA, local people who were trained for a 372-hours course on basic traditional Thai massage skill and additional training for basic rehabilitation practice. The TTMPA made 1-2 home visits a week for each patient to provide massage and basic rehabilitation therapy. The results showed that with additional home rehabilitation service by the TTMPA, the clinical outcomes of the patients measured by Modified Rankin Scale improved and the incidence of complications e.g. bed sore, pneumonia and urinary tract infection decreased. In conclusion, home massage and rehabilitation services by TTMPA had a potential role in helping functionality improvement for bed-ridden patients. Further long-term effectiveness of the service should be evaluated.